Pregestational body mass index, trimester-specific weight gain and total gestational weight gain: how do they influence perinatal outcomes?. (18th April 2021) - Gonzalez-Ballano, Isabel; Saviron-Cornudella, Ricardo; Esteban, Luis Mariano; Sanz, Gerardo; Castán, Sergio
Abstract: Objective: To investigate the association between pre-gestational body mass index (BMI), total gestational weight gain (GWG), and/or trimester-specific weight gain (GWGT) with adverse maternal or perinatal outcomes (AMPOs). Materials and methods: Maternal clinical characteristics and pregnancy and perinatal outcomes were used to predict AMPOs. The predictive ability of BMI, GWG, or GWGT for AMPOs was analyzed using the area under the curve (AUC). Logistic regression models in a univariate and multivariate analysis were performed to estimate the odds ratios (OR) and 95% confidence intervals (CI) to predict maternal outcomes (pregnancy-induced hypertension, preeclampsia or gestational diabetes mellitus) and perinatal outcomes (small for gestational age, large for gestational age, 5-min Apgar score, admission to neonatal intensive care unit or umbilical cord pH <7.15). Results: Women with AMPOs ( n  = 293) were younger with higher rate of nulliparity ( p  < .001) and with lower height ( p  = .018) as compared to controls ( n  = 134). In the univariate study, GWGT in third trimester was associated with double risk of pregnancy-induced hypertension (OR 2.00; 95% CI, 1.01–3.97). Nonetheless, third-trimester GWG and total GWG have a negative relationship with gestational diabetes mellitus OR 0.32 (95% CI, 0.18–0.58) and OR 0.35 (95% CI, 0.21–0.59), respectively. Women with greater overall and in second trimester, GWG have a lower risk of having SGA neonates, OR 0.62 (95% CI, 0.39–0.98) and OR 0.60 (95% CI, 0.37–0.98), respectively. In the multivariate study, pre-gestational BMI is strongly related to the development of preeclampsia and the area under the curve (AUC) of the combination of pre-gestational BMI and total weight gain was 0.832 (95% CI, 0.63–0.81) for preeclampsia and 0.719 (95% CI, 0.71–0.94) for gestational diabetes mellitus. Conclusion: Our results suggest than timing of gestational weight gain influence in maternal and perinatal outcomes. Pre-gestational BMI is a determinant of preeclampsia, maternal weight gain in the third trimester is a determinant of pregnancy-induced hypertension and the increase in total GWG reduces the risk of gestational diabetes mellitus and small for gestational age.